Miss Brown is Upside Down! : My Weirdest School Series #3 - Gutman, Dan; Paillot, Jim (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2015)
With guidance from Miss Brown, a teacher who is an expert on creativity, the third grade class at Ella Mentry School builds a car and a bridge to compete in a Brain Games competition against Dirk School.
Keywords: Schools -- Fiction; Teachers -- Fiction; Creative ability -- Fiction; Contests -- Fiction; Humorous fiction